Workshop TOEFL untuk Meningkatkan Kompetensi Guru Pesantren dan Calon Guru Bahasa Inggris - Ahmad Jailani; Sri Kamaliasari (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
English teacher competence is one of the crucial factors in achieving success in English education. Therefore, the competence of teachers and prospective teachers must continuously be improved by giving trainings related to English language and English language teaching. The PkM team tried to improve the language skills of Islamic boarding school teachers and prospective teachers by giving TOEFL workshop. Specifically, this study explains how the workshop was conducted, the improvement in participants' TOEFL abilities before and after the workshop, and participants' responses to the TOEFL workshop activities. This activity involved 22 participants. The workshop began with a pre-test to assess participants' initial abilities, followed by 14 hours of instructional sessions, and concluded with a post-test to measure the improvement in participants' abilities, along with a questionnaire to evaluate their perceptions and responses to the activity. The analysis results revealed that the workshop was conducted smoothly using interactive and practice-based methods. The pre-test and post-test data indicated a significant improvement in participants' TOEFL scores after attending the workshop. Moreover, the participants' responses to the activity were very positive, with the majority stating that the workshop was relevant, beneficial, and boosted their confidence in understanding TOEFL material. This TOEFL workshop successfully contributed to enhancing participants' English language competence and received positive feedback from the participants. Similar activities are recommended to be conducted regularly to support the professional development of educators and prospective educators in Bengkalis Districk.